Species-richness in the Oriental fungus-feeding thrips of the genus Azaleothrips (Thysanoptera, Phlaeothripidae) - Okajima, Shûji; Masumoto, Masami (Zootaxa, 2014)
Azaleothrips, a phlaeothripine genus of fungus-feeding species, is presumably endemic to the Oriental Region between India and Japan. Although only 10 species have been known in this genus until now, a total of 35 species is recorded here, of which 26 are newly described: from Indonesia—A. bali sp.n., A. bulelengi sp.n., A. dentatus sp.n., A. dorsalis sp.n., A. floresi sp.n., A. inflavus sp.n., A. simulans sp.n., A. sulawesicus sp.n., from the Philippines—A. apoensis sp.n., A. bifidius sp.n., A. luzonensis sp.n., A. mindanaoensis sp.n., A. philippinensis sp.n., from Taiwan—A. atayal sp.n., A. formosae sp.n., A. taiwanus sp.n., from Thailand—A. flavicollis sp.n., A. phuketanus sp.n., A. pulcher sp.n., A. toshifumii sp.n., from Vietnam—A. laocai sp.n., A. vietnamensis sp.n., from W. Malaysia—A. malaya sp.n., A. reticulatus sp.n., A. richardi sp.n., A. templeri sp.n. In addition A. magnus Chen, described from Taiwan, is newly synonymized with A. moundi. Azaleothrips laevigatus, described from southern Japan, is newly recorded more widely in Southeast Asia. A key to 33 species is provided, but A. bhattii and A. lineus cannot be recognized because of the poor information in the original descriptions.